Fiona and jane eaudiobook - Ho, Jean Chen (Penguin Audio, 2022)
A TIME , NPR, VOGUE , OPRAH DAILY , AND VULTURE BEST BOOK OF THE YEAR (SO FAR) One of TIME ’s 100 Must-Read Books of 2022 “Ho's debut work is the perfect modern example of great American fiction. . . . You will love it.” —Jake Tapper “Intimate, cinematic. . . . The world Ho creates between the two women feels like one friend reading the other’s story, wishing she were there.” — The New York Times Book Review “[ Fiona and Jane ] is about an incredible lifelong friendship between two Asian American women growing up in Southern California—absolutely adored that book.” —Ailsa Chang, NPR’s “All Things Considered” “Intricately rendered. . . . Fiona and Jane celebrates a woman’s ability to be late, to show up in their own lives when and where they want to, to change their minds, to be lonely and to be in love, and to be respected regardless.” — The Washington Post A witty, warm, and irreverent book that traces the lives of two young Taiwanese American women as they navigate friendship, sexuality, identity, and heartbreak over two decades. Best friends since second grade, Fiona Lin and Jane Shen explore the lonely freeways and seedy bars of Los Angeles together through their teenage years, surviving unfulfilling romantic encounters, and carrying with them the scars of their families' tumultuous pasts. Fiona was always destined to leave, her effortless beauty burnished by fierce ambition—qualities that Jane admired and feared in equal measure. When Fiona moves to New York and cares for a sick friend through a breakup with an opportunistic boyfriend, Jane remains in California and grieves her estranged father's sudden death, in the process alienating an overzealous girlfriend. Strained by distance and unintended betrayals, the women float in and out of each other's lives, their friendship both a beacon of home and a reminder of all they've lost. In stories told in alternating voices, Jean Chen Ho's debut collection peels back the layers of female friendship—the intensity, resentment, and boundless love—to probe the beating hearts of young women coming to terms with themselves, and each other, in light of the insecurities and shame that holds them back. Spanning countries and selves, Fiona and Jane is an intimate portrait of a friendship, a deep dive into the universal perplexities of being young and alive, and a bracingly honest account of two Asian women who dare to stake a claim on joy in a changing, contemporary America. NAMED A MOST ANTICIPATED BOOK OF 2022 BY VOGUE * USA TODAY * TIME * OPRAH DAILY * PARADE * THE WASHINGTON POST * BUZZFEED * GOOD HOUSEKEEPING * MARIE CLAIRE * FORTUNE * GLAMOUR * W MAGAZINE * NYLON * BUSTLE * POPSUGAR * ELECTRIC LITERATURE * THE RUMPUS * DEBUTIFUL * AND MORE!